2012
DOI: 10.1186/1471-2431-12-37
|View full text |Cite
|
Sign up to set email alerts
|

Development of lung function in very low birth weight infants with or without bronchopulmonary dysplasia: Longitudinal assessment during the first 15 months of corrected age

Abstract: BackgroundVery low birth weight (VLBW) infants (< 1,500 g) with bronchopulmonary dysplasia (BPD) develop lung damage caused by mechanical ventilation and maturational arrest. We compared functional lung development after discharge from hospital between VLBW infants with and without BPD.MethodsComprehensive lung function assessment was performed at about 50, 70, and 100 weeks of postmenstrual age in 55 sedated VLBW infants (29 with former BPD [O2 supplementation was given at 36 weeks of gestational age] and 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 45 publications
4
33
1
3
Order By: Relevance
“…PULMONARY PERSPECTIVE studies used case-control methods (26,30,33,46,51,61,64,65,74), five were longitudinal prospective cohort studies (21,27,55,58,73), and the remaining studies used retrospective cohort designs (26,31,40,47). Overall, it was found that in the first 5 years of life, children with a diagnosis of BPD showed signs of substantial airway functional impairment as exhibited by abnormal measures of FEV, VC, and FRC.…”
Section: N = 90mentioning
confidence: 96%
See 2 more Smart Citations
“…PULMONARY PERSPECTIVE studies used case-control methods (26,30,33,46,51,61,64,65,74), five were longitudinal prospective cohort studies (21,27,55,58,73), and the remaining studies used retrospective cohort designs (26,31,40,47). Overall, it was found that in the first 5 years of life, children with a diagnosis of BPD showed signs of substantial airway functional impairment as exhibited by abnormal measures of FEV, VC, and FRC.…”
Section: N = 90mentioning
confidence: 96%
“…In one study, infants with above average somatic growth showed greater improvements in lung function with longitudinal assessments (57). Additionally, after adjusting for differences in weight, VT and V : E, children with a diagnosis of BPD appear to develop similarly to children without BPD (58,65). Evidence of catch-up during the first 15 months of life was only found when tidal breathing parameters, VT and V : E, were measured in this study population (65).…”
Section: N = 90mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 articles included (table 1), 12 assessed children with a history of BPD at different moments (longitudinal) [7][8][9][10][11][12][13][14][15][16]27,28 and the maximum follow-up was the interval between the neonatal hospital stay and five years of life. The remaining ten reviewed studies performed pulmonary function testing in one single moment (transversal).…”
Section: Resultsmentioning
confidence: 99%
“…In this review, the studies suggest that respiratory symptoms and pulmonary function seem to improve in early childhood 7,8,10,12,27 with the growth and development of the child with a history of BPD. Farstad et al 12 found that, at 50 weeks of corrected age (CA), 80% of the children with BPD in their study sample had severe peripheral obstruction, compared to 58% of preterm infants without BPD.…”
Section: Discussionmentioning
confidence: 99%